Prevention of High-Dose Cytosine Arabinoside-Induced Acute Pericarditis with Preemptive Dexamethasone Administration: A Case Report and Literature Review - Weerapat Owattanapanich; Theera Ruchutrakool (Case Reports in Hematology)
Pericarditis/pericardial effusion (PC/PEEF) is a rare but fatal complication of cytosine arabinoside (Ara-C). We report an acute myeloid leukemia (AML) patient who developed massive pericardial effusion after a second Ara-C exposure. As Ara-C was most beneficial in controlling the leukemia, she was treated with a further cycle of Ara-C along with dexamethasone to prevent the complication from reoccurring. No PC/PEEF was subsequently detected.